1995
DOI: 10.1021/bi00017a009
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Refolding and Reoxidation of Recombinant Porcine Growth Hormone from a Urea Denatured State and from Escherichia coli Inclusion Bodies

Abstract: Overexpression of cloned genes in bacteria often leads to insoluble refractile body formation requiring solubilization and refolding to obtain biologically active proteins. A refolding pathway was established for a model protein, porcine growth hormone (PGH), yielding an appreciably high recovery of 85%. The conditions include the dilution of a urea, beta-mercaptoethanol (beta-ME) denatured PGH solution in a refolding environment containing 3.5 M urea and 10 mM beta-ME/HED at a 10:1 ratio at pH 9.1 and 0.5 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 42 publications
0
17
0
1
Order By: Relevance
“…Chaotropic agents such as urea, guanidine hydrochloride (Gdn-HCl) 2 , and thiocyanate salts (8,9), detergents such as sodium dodecyl sulfate (SDS) (10), N-cetyltrimethylammonium chloride (11) and sarkosyl (sodium N-lauroyl sarcosine; NLS) (12) along with reducing agents like ␤-mercaptoethanol, dithiothreitol, or cysteine have been extensively used for solubilizing the inclusion body proteins. The soluble proteins are then refolded to their native state after the chaotropic agents or other salts are removed by dialyzing the proteins in buffers containing reducing and oxidizing agents (8,13).…”
Section: High-level Expression Of Recombinant Proteins Inmentioning
confidence: 99%
“…Chaotropic agents such as urea, guanidine hydrochloride (Gdn-HCl) 2 , and thiocyanate salts (8,9), detergents such as sodium dodecyl sulfate (SDS) (10), N-cetyltrimethylammonium chloride (11) and sarkosyl (sodium N-lauroyl sarcosine; NLS) (12) along with reducing agents like ␤-mercaptoethanol, dithiothreitol, or cysteine have been extensively used for solubilizing the inclusion body proteins. The soluble proteins are then refolded to their native state after the chaotropic agents or other salts are removed by dialyzing the proteins in buffers containing reducing and oxidizing agents (8,13).…”
Section: High-level Expression Of Recombinant Proteins Inmentioning
confidence: 99%
“…We report here studies designed to test the validity of the hinge opening hypothesis by using a strategy that tethers the helix bundle by means of a disulfide bond and is hypothesized to prevent its proposed opening during lipoprotein interaction (Breiter et al, 1991). Site-directed introduction of non-natural intramolecular disulfide bonds has proven to be a valuable tool for obtaining information about protein conformational changes (Duche et al, 1994;Chang and Cronan, 1995), folding (Cardamone et al, 1995), stability (Wetzel et al, 1988;, and proximity relationships (Wolff-Long et al, 1995). We have introduced two cysteines into M. sexta apoLp-III (which otherwise lacks cysteine) by site-directed mutagenesis at strategic locations postulated to facilitate and maximize the probability of intramolecular disulfide bond formation.…”
mentioning
confidence: 99%
“…The renaturation of protein aggregates in bacterial inclusion bodies into biologically active conformations involves a number of interdependent steps: solubilization, oxidative refolding, and withdrawal of denaturants, each of which represents a challenge of strategy and optimization (Handl et al 1993, Cardamone et al 1995. In the present study, we determined that a strong ionic denaturant, 6 M guanidine, was more effective than 8 M urea in solubilizing the inclusion bodies.…”
Section: Discussionmentioning
confidence: 74%
“…However, in evaluating the recoveries from subsequent refolding steps, we found that the rhbFGF activity recovered from guanidine-HC1 solutions was much lower than from urea. Others also have reported that guanidine-HC1 may interfere with the refolding process (Cardamone et al 1995). For this reason, we utilized guanidine-HC1 initially as a denaturant to solubilize the inclusion bodies and optimize the recovery of the recombinant proteins and then replaced the 6 M guanidine-HCt with 8 M urea in the course of affinity purification.…”
Section: Discussionmentioning
confidence: 99%